2020
DOI: 10.1007/s40264-019-00898-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the National Pharmacovigilance Systems in East Africa: Ethiopia, Kenya, Rwanda and Tanzania

Abstract: Introduction The increased access to medicinal products in Africa is not well-matched with the pharmacovigilance capacity to monitor drug safety. The objective of this study was to assess the functionality and identify the strengths and limitations of the national pharmacovigilance systems in Ethiopia, Kenya, Rwanda, and Tanzania, and compare these systems. Methods Legal and statutory documents governing the pharmacovigilance systems of each participating country were examined by assessors prior to on-site rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 11 publications
2
65
0
Order By: Relevance
“…This proportion is low in Iran compared to many developed countries, [34][35][36][37][38][39] ranging from 17.0 to 323.0 per 100 000 population. Nonetheless, this proportion was higher in Iran than in Turkey, 40 Kenya, Ethiopia, and Tanzania, 41 which was 0.4 to 3.5 per 100 000 population. Aagaard et al's study showed that high-income countries had the highest proportions of ADR reporting and low-income countries the lowest, with large variations observed across countries.…”
Section: Discussionmentioning
confidence: 88%
“…This proportion is low in Iran compared to many developed countries, [34][35][36][37][38][39] ranging from 17.0 to 323.0 per 100 000 population. Nonetheless, this proportion was higher in Iran than in Turkey, 40 Kenya, Ethiopia, and Tanzania, 41 which was 0.4 to 3.5 per 100 000 population. Aagaard et al's study showed that high-income countries had the highest proportions of ADR reporting and low-income countries the lowest, with large variations observed across countries.…”
Section: Discussionmentioning
confidence: 88%
“…This rate is low in Iran compared to many developed countries, [51][52][53][54][55][56] with rates ranging from 17.0 to 323.0 per 100 000 population. Nonetheless, the rate was higher in Iran than in Turkey, 57 Ethiopia, 58 Kenya, and Tanzania, 59 which was 0.4 to 3.5 per 100 000 population. Furthermore, medicine-related death is a measure of the harmful effects of medicines in the community on hospitalized or non-hospitalized patients.…”
Section: Discussionmentioning
confidence: 90%
“…The NTD programs and national pharmacovigilance centers should plan and conduct the abovementioned pharmacovigilance activities to avoid duplication of efforts and optimize the use of resources [ 23 ]. Collaboration with other partners, such as academic institutions and researchers, can further strengthen safety monitoring by conducting pharmacovigilance studies of public health importance [ 25 , 30 ]. Such collaborative safety surveillance would provide information on the safety of the treatment regimens, the true incidence of ADRs, the risk factors, and the tolerance in patients at risk for ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…Zero ICSRs associated with medicines used in MDA for targeted NTDs were submitted in the last calendar year (2017/2018). In 2017/2018, the majority of ICSRs that were submitted to the national pharmacovigilance center in Ethiopia and Kenya were from the tuberculosis and HIV/AIDS programs [ 30 ]. Unlike the malaria, tuberculosis, and HIV programs, drugs in NTD programs are given through MDA to all at-risk populations without prior diagnosis or screening, with no possibility of post-MDA follow-up for timely identification and management of AEs.…”
Section: Discussionmentioning
confidence: 99%